A comparative study on the effects of amphiphilic and hydrophilic polymers on the release profiles of a poorly water-soluble drug. (17th February 2016) - Irwan, Anastasia W.; Berania, Jacqueline E.; Liu, Xueming
Abstract: This paper reports the use of two crystalline polymers, an amphiphilic Pluronic® F-127 (PF-127) and a hydrophilic poly(ethylene glycol) (PEG6000) as drug delivery carriers for improving the drug release of a poorly water-soluble drug, fenofibrate (FEN), via micelle formation and formation of a solid dispersion (SD). In 10% PF-127 (aq.), FEN showed an equilibrium solubility of ca. 0.6 mg/mL, due to micelle formation. In contrast, in 10% PEG6000 (aq.), FEN only exhibited an equilibrium solubility of 0.0037 mg/mL. FEN-loaded micelles in PF-127 were prepared by direct dissolution and membrane dialysis. Both methods only yielded a highest drug loading (DL) of 0.5%. SDs of FEN in PF-127 and PEG6000, at DLs of 5–80%, were prepared by solvent evaporation. In-vitro dissolution testing showed that both micelles and SDs significantly improved FEN's release rate. The SDs of FEN in PF-127 showed significantly faster release than crystalline FEN, when the DL was as high as 50%, whereas SDs of PEG6000 showed similar enhancement in the release rate when the DL was not more than 20%. The DSC thermograms of SDs of PF-127 exhibited a single phase transition peak at ca. 55–57 °C when the DL was not more than 50%, whereas those in PEG6000 exhibited a similar peak at ca. 61–63 °C when the DL was not more than 35%. When the DL exceeded 50% for SDs of PF-127 and 35% for SDs of PEG6000, DSC thermograms showed two melting peaks for the carrier polymer and FEN, respectively. FT-IR studies revealed that PF-127 has a stronger hydrophobic–hydrophobic interaction with FEN than PEG6000. It is likely that both dispersion and micelle formation contributed to the stronger effect of PF-127 on enhancing the release rate of FEN in its SDs.